Mediated discourses : Ethnic minority media in linguistic and ethnic identity-building and language revitalization : Comparative case studies from Finno- Ugrian minority contexts - Tánczos, Outi (Helsingin yliopisto, 2018)
The dissertation consists of six peer-reviewed articles and an introduction that presents the background, objectives and results of the study. The thesis investigates the issues of representations of languages and ethnicities and division of power and responsibility in terms of language maintenance. The study takes a comparative perspective and analyzes material from several languages, most notably Karelian in the Republic of Karelia in Russia, but also Hungarian in Transylvania and Veps in Russia. The languages were chosen because of the similarities in their revival history, mainly the language political turn in the late 1980s, and the considerable differences in their societal status and ethnolinguistic vitality. A critical discourse analytic approach is applied, combining linguistic analysis with sociolinguistic background knowledge. The data of this study consist of newspaper texts published in several minority language newspapers during the period 1998–2011 and of research interviews of two types: focus group interviews carried out in the ELDIA project (2010–2013) and individual interviews of editors-in-chief of three minority language newspapers, Oma Mua (Karelian), Szabadság (Transylvanian Hungarian) and Kodima (Veps). The study contributes to the less-studied field of critical media discourse studies in Finno-Ugrian studies. It provides insight into the conventions of minority media making in different social and political contexts. The findings suggest that since the beginning of its revival in the 1990s, the primary role of the Karelian language has become transformed from an everyday means of communication to a means of ethnos-making. In the minority language newspaper, language is a central topic which functions as a symbol and component of ethnic identity. The minority rights framework is only present to a small extent, and the focus lies on tradition, culture and the role of language in these newspapers. Minority language newspapers published in Russia share many similarities. The Transylvanian ...